Modern Jewish thinkers : from Mendelssohn to Rosenzweig - Greenberg, Gershon (Brighton, Mass. : Academic Studies Press, 2011)
Historical conditions at the end of the eighteenth century opened an arena between the formerly autonomous Jewish community and the Christian world, which yielded new departure points for philosophy, including revelation and philosophical reason, dialectically considered; rationalism as intellection and advancing consciousness, heteronymous revelation, historicity, and universal morality. In Modern Jewish Thinkers, Greenberg restructures the history of modern Jewish thought comprehensively, providing first-time English translations of Reggio, Krokhmal, Maimon, Samuel Hirsch, Formstecher, Steinheim, Ascher, Einhorn, Samuel David Luzzatto and Hermann Cohen. The availability of these sources fills a gap in the field and stimulates new directions for teaching and scholarly research in modern Jewish thought, going beyond Spinoza and Mendelssohn at one end, and to popular 20th century figures on the other. --From publisher's description.
The dialectical truth -- Intellection and developing consciousness -- Heteronomous revelation -- History -- Universal morality -- Through the twentieth century.
Includes bibliographical references and index.
Master record variable field(s) change: 650
Keywords: Jewish philosophy; PHILOSOPHY -- Eastern; Jewish philosophy; Electronic books